2009
DOI: 10.1097/sla.0b013e31818e43ab
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Surgical Treatments for Achalasia

Abstract: EBD is superior to EBTI. Laparoscopic myotomy with fundoplication was the most effective surgical technique and can be considered the operative procedure of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
477
3
60

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 632 publications
(576 citation statements)
references
References 102 publications
(32 reference statements)
27
477
3
60
Order By: Relevance
“…Studies initially showed superiority of surgical myotomy in terms of efficiency and durability compared to single balloon dilatation [35,36]. Further comparison of these two modalities has shown similar outcomes in treatment success rates after 2-year follow-up when a graded approach to PD has been used [32,37,38]. Pneumatic balloon dilatation and surgical myotomy therefore remain the universally accepted treatments for achalasia presently, and patients should be followed up long term [39].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies initially showed superiority of surgical myotomy in terms of efficiency and durability compared to single balloon dilatation [35,36]. Further comparison of these two modalities has shown similar outcomes in treatment success rates after 2-year follow-up when a graded approach to PD has been used [32,37,38]. Pneumatic balloon dilatation and surgical myotomy therefore remain the universally accepted treatments for achalasia presently, and patients should be followed up long term [39].…”
Section: Treatmentmentioning
confidence: 99%
“…Surgical LES myotomy also disrupts the LES fibers with a longitudinal incision. The preferred method has been the laparoscopic approach, or laparoscopic Heller myotomy (LHM), due to decreased morbidity and faster recovery [31,32]. Though this method effectively relieves the obstruction, it also increases the risk of gastroesophageal reflux, and most surgeons incorporate an anti-reflux procedure by way of a partial fundoplication [33,34].…”
Section: Treatmentmentioning
confidence: 99%
“…Many studies suggest and reccomend to use a graded dilator approach, given the good to excellent relief of symptoms in 50-93% of the treated patients (42)(43)(44).…”
Section: Pneumatic Dilationmentioning
confidence: 99%
“…Laparoscopic Heller myotomy (LHM) improves the symptoms of patients. The reported clinical success rate is 89% (range 76-100%) [9]. The most common post-myotomy complication is gastro-esophageal reflux disease (GERD).…”
mentioning
confidence: 99%